Thin molecular films of supramolecular porphyrins - Koiti Araki (Anais da Academia Brasileira de Ciências, 2000)
Arelevant series of symmetric supramolecular porphyrins has been obtained by attaching four [RuII(bipy)2Cl]groups to the pyridyl substituents of meso-tetra(4-pyridyl)porphyrin and its metallated derivatives. Thesecompounds display a rich electrochemistry and versatile catalytic, electrocatalytic and photochemical properties,associated with the ruthenium-bipyridine and the porphyrin complexes. These properties can betransferred to the electrodes by attaching thin molecular films of the compounds, by dip-coating, electrostaticassembly or electropolymerization. In this way, the interesting properties of those supermolecules andsupramolecular assemblies can be used to prepare molecular devices and sensors.